STRUCTURAL TOPOLOGY REANALYSIS FOR TWICE CONTINUOUS MODIFICATIONS BASED ON COUPLED CONDENSATION - HE JianJun; CHEN XiangZi (Jixie qiangdu)
According to the problem of structural dynamical topological reanalysis for continuous two modifications,a new method for dynamic reanalysis of topological modified structure with added degrees and two continuous modifications was proposed in this paper,which is combined independent mass orthogonalization strategy with Rayleigh-Ritz analysis and the coupled condensation method. Comparing with the direct finite element analysis（ FEA）,the high computational effort for FEA is greatly decreased by utilizing the proposed reanalysis procedures,which is also easy to operate and implement. The numerical example shows that the proposed method for dynamical topological reanalysis of continuous two modifications is effective.